(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Fish drying is an age old practice and was adopted as a practical method of preserving fish that have not been immediately consumed or sold in the fresh market. Improved fishing techniques and infrastructure resulted in increased fish catch, better marketing, processing and curing facilities. The advent of multiday trawling at the Visakhapatnam Fishing Harbour further boosted the availability of fish and its processing into value added products. However, drying still remains the cheapest and popular mode of fish preservation. Irradiation has distinct advantages over other commercial methods of pest control. Apart from being less energy consuming than fumigation, it does not leave toxic residues in the product. It has been observed that a dose of 0.5 kGy can effectively disinfest dried fish and fishery products at a moisture level of below 40.